2008
DOI: 10.1177/1049732308327242
|View full text |Cite
|
Sign up to set email alerts
|

Children's Pain Assessment in Northeastern Thailand: Perspectives of Health Professionals

Abstract: Deficiencies in pain care within the developing world are starting to be realized. Children, in particular, are vulnerable, as preliminary studies suggest that these children receive less pain treatment because of health professionals' attitudes and beliefs. This article reports on some of the findings of the first study in a larger program of research aimed at improving pediatric pain care in Thailand. Improvements in practice are not simply the result of providing evidenced-based knowledge, but a complex pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
0
31
0
1
Order By: Relevance
“…Azam, Campbell, and Ross () explored the burden of pain in children and suggested that pain is a significant unaddressed problem in children with HIV/AIDS. Several studies indirectly estimated the burden of paediatric pain in LMIC by examining health care provider's knowledge, attitude, and experiences in paediatric pain management (Dongara, Shah, Nimbalkar, Phatak, & Nimbalkar, ; Ekim & Ocakci, ; Finley, Forgeron, & Arnaout, ; Forgeron et al, ; He et al, ; He, Vehviläinen‐Julkunen, Pietilä, & Pölkki, ; Huth, Gregg, & Lin, ; Katende & Mugabi, ; Lunsford, ; Mathew, Mathew, & Singhi, ). The results from these studies suggest a low level of knowledge, unfavourable attitudes towards children's pain and pain management and high prevalence of myths and misconceptions which are often associated with inadequate pain management.…”
Section: Resultsmentioning
confidence: 99%
“…Azam, Campbell, and Ross () explored the burden of pain in children and suggested that pain is a significant unaddressed problem in children with HIV/AIDS. Several studies indirectly estimated the burden of paediatric pain in LMIC by examining health care provider's knowledge, attitude, and experiences in paediatric pain management (Dongara, Shah, Nimbalkar, Phatak, & Nimbalkar, ; Ekim & Ocakci, ; Finley, Forgeron, & Arnaout, ; Forgeron et al, ; He et al, ; He, Vehviläinen‐Julkunen, Pietilä, & Pölkki, ; Huth, Gregg, & Lin, ; Katende & Mugabi, ; Lunsford, ; Mathew, Mathew, & Singhi, ). The results from these studies suggest a low level of knowledge, unfavourable attitudes towards children's pain and pain management and high prevalence of myths and misconceptions which are often associated with inadequate pain management.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, research on paediatric pain has improved in the last several years, and dentists should use this evidence to support their practice, especially for pain assessment in children. Non‐standardised pain assessment results in the under‐recognition of pain, precluding appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates prompt notification of and response to pain problems and adequate handover between staff. Nursing staff should be encouraged to communicate their concerns as hierarchical structures often impede the flow of important information .…”
Section: The Ideal Acute Pain Servicementioning
confidence: 99%
“…Nursing staff competency, the nurse‐to‐patient ratio and the availability of delivery equipment and monitoring will determine which analgesic techniques can be safely administered in any given hospital environment. Private or semi‐private rooms may require a centralized monitoring system unless the nurse‐to‐patient ratio is very high, a luxury not available in many areas of the world where open wards are necessary for safe observation .…”
Section: The Ideal Acute Pain Servicementioning
confidence: 99%